Nonequidistant antenna arrays synthesis based on genetic algorithm - Oznobikhin, V I; Romodin, V B; Shebalkova, L V (IOP conference series. Materials Science and Engineering, 2021)
A new approach to the synthesis of nonequidistant antenna arrays with uniform distribution based on the Genetic Algorithm of the global extrema search is introduced and analyzed. The technique is demonstrated for various uniform antenna array structure. The radiation pattern of the nonequidistant antenna array is formed using the Genetic Algorithm to reduce a side lobe level. A mathematical formula is presented to highlight the operation of objective function minimization.